Missed opportunities in preventing mother-to-child transmission of syphilis in the indigenous population in central Brazil - Renata Palópolí Pícoli; Luiza Helena de Oliveira Cazola (Instituto Materno Infantil de Pernambuco, 2023)
Abstract Objectives: to estimate the detection rate of syphilis in pregnant women, the occurrence of congenital syphilis, and the rate of mother-to-child transmission of syphilis, in addition to analyzing missed opportunities in the prevention of mother-to-child transmission in the indigenous population. Methods: descriptive study of cases of pregnant indigenous women with syphilis resulting or not in a case of congenital syphilis. The data were obtained from the Sistema de Informação de Agravos de Notificação (Information System of Notifable Diseases), the records of the Infecções Sexualmente Transmissíveis do Distrito Sanitário Especial Indígena (Sexually Transmitted Infections in the Special Indigenous Health District), and the medical records of pregnant indigenous women in 2015. The database and the calculation of syphilis rates in pregnant women, congenital syphilis, and mother-to-child transmission were carried out. Data on prenatal, diagnosis and treatment of syphilis during pregnancy were collected from the medical records. Results: the detection rate of syphilis in pregnant women reached 35.2/1,000 live births (LB), the occurrence of congenital syphilis encompassed 15.7/1.000 LB, and the rate of mother-to-child transmission was 44.8%. Six (24%) pregnant women started prenatal care in the first trimester and seven (28%) attended seven or more consultations. The diagnosis of syphilis was late and only nine (36%) women were properly treated. Conclusions: failures in the diagnosis and the adequate treatment of pregnant women with syphilis compromised the prevention of mother-to-child transmission of the disease.